N6-Methyladenosine Methylomic Landscape of Lung Tissues in Murine Acute Allergic Asthma - Teng, Fangzhou; Tang, Weifeng; Wuniqiemu, Tulake; Qin, Jingjing; Zhou, Yaolong; Huang, Xi; Wang, Shiyuan; Zhu, Xueyi; Tang, Zhao; Yi, La; Wei, Ying; Dong, Jingcheng (Frontiers in Immunology, 2021)
Allergic asthma is well known as a common respiratory disorder comprising an allergic inflammatory nature and excessive immune characteristic. N6-methyladenosine (m6A) methylation is an RNA epigenetic modification that post-transcriptionally regulates gene expression and function by affecting the RNA fate. Currently, m6A methylation is gaining attention as a mechanism of immunoregulation. However, whether m6A methylation engages the pathological process of asthma remains uncertain. Here, we present the m6A methylomic landscape in the lung tissues of ovalbumin-induced acute asthma mice using MeRIP-seq and RNA-seq. We identified 353 hypermethylated m6A peaks within 329 messenger RNAs (mRNAs) and 150 hypomethylated m6A peaks within 143 mRNAs in the lung tissues of asthmatic mice. These differentially methylated mRNAs were found to be involved in several immune function-relevant signaling pathways. In addition, we predicted 25 RNA-binding proteins that recognize the differentially methylated peak sites by exploring public databases, and the roles of these proteins are mostly related to mRNA biogenesis and metabolism. To further investigate the expression levels of the differentially methylated genes, we performed combined analysis of the m6A methylome and transcriptome data and identified 127 hypermethylated mRNAs (107 high and 20 low expression) and 43 hypomethylated mRNAs with differential expressions (9 high and 34 low expression). Of these, there are a list of mRNAs involved in immune function and regulation. The present results highlight the essential role of m6A methylation in the pathogenesis of asthma.